LIM-kinase 1 effects on memory abilities and male courtship song in Drosophila depend on the neuronal type - A. V. Zhuravlev; E. S. Zalomaeva; E. S. Egozova; A. D. Emelin; V. V. Sokurova; E. A. Nikitina; E. V. Savvateeva-Popova (Вавиловский журнал генетики и селекции)
The signal pathway of actin remodeling, including LIM-kinase 1 (LIMK1) and its substrate cofilin, regulates multiple processes in neurons of vertebrates and invertebrates. Drosophila melanogaster is widely used as a model object for studying mechanisms of memory formation, storage, retrieval and forgetting. Previously, active forgetting in Drosophila was investigated in the standard Pavlovian olfactory conditioning paradigm. The role of specific dopaminergic neurons (DAN) and components of the actin remodeling pathway in different forms of forgetting was shown. In our research, we investigated the role of LIMK1 in Drosophila memory and forgetting in the conditioned courtship suppression paradigm (CCSP). In the Drosophila brain, LIMK1 and p-cofilin levels appeared to be low in specific neuropil structures, including the mushroom body (MB) lobes and the central complex. At the same time, LIMK1 was observed in cell bodies, such as DAN clusters regulating memory formation in CCSP. We applied GAL4 × UAS binary system to induce limk1 RNA interference in different types of neurons. The hybrid strain with limk1 interference in MB lobes and glia showed an increase in 3-h short-term memory (STM), without significant effects on long-term memory. limk1 interference in cholinergic neurons (CHN) impaired STM, while its interference in DAN and serotoninergic neurons (SRN) also dramatically impaired the flies’ learning ability. By contrast, limk1 interference in fruitless neurons (FRN) resulted in increased 15–60 min STM, indicating a possible LIMK1 role in active forgetting. Males with limk1 interference in CHN and FRN also showed the opposite trends of courtship song parameters changes. Thus, LIMK1 effects on the Drosophila male memory and courtship song appeared to depend on the neuronal type or brain structure.